Searching for pale, getting rickets - Bamashmus, Said; Bamosmoosh, Mohamed; Modesti, Pietro Amedeo (Springer Nature, 2010)
A 36-year-old woman presented with her 2-year child in the out-patient orthopaedic department of our hospital. She complained that her little boy was unable to walk properly without support. The child looked intelligent, aware of what was happening around him. However he was hypotonic with muscular weakness, cranial sutures were still widened and dental eruption was delayed. No other abnormal findings were found at the physical examination. Urine and essential blood tests were normal except for an increase in the serum alkaline phosphatase (1,253 IU/ml). The X-ray performed to his legs showed radiologic alteration at the epiphyseal growth plate due to decreased calcification of the hypertrophic zone and inadequate mineralization of the primary spongiosa. The orthopaedist asked to visit also the 15-year-old sister who was accompanying the little infant. The young woman had skeletal pain and most significantly a rachitic rosary due the prominence of the costochondral junctions. These findings confirmed the suspect of the orthopaedist and he diagnosed in both patients the presents of rickets. While speaking with the mother he found out that she wanted her children to be as much white as possible and did not let them get in contact with sunlight and obliged her daughter to dress the dark nighab since an early age. The physician advised the mother to give her children food rich with calcium and oral vitamin D, but explained and convinced her that sunlight is more important for the good health of her children than any other treatment. At the 6 months follow up, the little boy was fine and able to walk correctly and the clinical findings for his sister were improving.